Reorientation Mechanisms of Graphene Coated Copper {001} Surfaces - Jian Song; Songsong Yao; Quan Li; Jiamiao Ni; Zhuoxin Yan; Kunming Yang; Guisen Liu; Yue Liu; Jian Wang (Metals, 2023)
Engineering the surface orientation of face-centered cubic (fcc) metals to the close-packed {111} plane can significantly enhance their oxidation resistance. However, owing to the synergetic effect of surface energy density (<semantics><mover accent="true">γ˙</mover></semantics>) and strain energy density (<semantics>ω</semantics>), such close-packed surface orientation can currently only be achieved by atomic-level thin film epitaxy or monocrystallization of polycrystalline metals. In this study, we characterized the microstructures of pure copper (Cu) foil and two types of graphene-coated Cu (Gr/Cu) foils and observed a 12~14 nm thick reconstructed surface layer with the {111} orientation in the high-temperature deposited Gr/{001} Cu surface. Combining the statistical results with thermodynamic analysis, we proposed a surface melting-solidification mechanism for the reconstruction of the Cu surface from {001} orientation to {111} orientation. This process is dominated by Gr/Cu interfacial energy and is particularly promoted by high-temperature surface melting. We also validated such a mechanism by examining Cu surfaces coated by h-BN (hexagonal boron nitride) and amorphous carbon. Our findings suggest a possible strategy to enhance the surface properties of fcc metals via engineering surface crystallography.